High Prevalence of Multidrug-Resistant Klebsiella pneumoniae in a Tertiary Care Hospital in Ethiopia - Tewachew Awoke; Brhanu Teka; Aminu Seman; Shemse Sebre; Biruk Yeshitela; Abraham Aseffa; Adane Mihret; Tamrat Abebe (MDPI AG, 2021)
Klebsiella pneumoniae poses an urgent public health threat, causing nosocomial outbreaks in different continents. It has been observed to develop resistance to antimicrobials more easily than most bacteria. These days, multidrug-resistant strains are being increasingly reported from different countries. However, studies on the surveillance of multidrug-resistant Klebsiella pneumoniae are very rare in Ethiopia. This study aimed to determine the antimicrobial resistance patterns and magnitude of MDR K. pneumoniae isolates from patients attending or admitted to Tikur Anbessa Specialized Hospital (TASH). A cross-sectional study was conducted from September 2018 to February 2019 at TASH, Addis Ababa, Ethiopia. Identification of K. pneumoniae was done by examining the Gram stain, colony characteristics on MacConkey agar and 5% sheep blood agar, as well as using a series of biochemical tests. Antimicrobial susceptibility testing of the isolates for 21 antimicrobials was done by the Kirby-Bauer disc diffusion technique. Data were double entered using Epidata 3.1 and exported to SPSS version 25 software for analysis. Among the total K. pneumoniae isolates (n = 132), almost all 130 (98.5%) were MDR. Two (1.5%) isolates showed complete non-susceptibility to all antimicrobial agents tested. Moreover, a high rate of resistance was observed to cefotaxime and ceftriaxone 128 (97%), trimethoprim-sulfamethoxazole 124 (93.9%), and cefepime 111 (84.1%). High susceptibility was recorded to amikacin 123 (93.2%), imipenem 107 (81.1%), meropenem 96 (72.7%), and ertapenem 93 (70.5%). K. pneumoniae isolates showed a high rate of resistance to most of the tested antimicrobials. The magnitude of MDR K. pneumoniae was very alarming. Therefore, strengthening antimicrobial stewardship programs and antimicrobial surveillance practices is strongly recommended in TASH.